Efficacy and safety of bortezomib in patients with renal impairment: results from the APEX phase 3 study - San-Miguel, Jesús F.; Richardson, P. G.; Sonneveld, P.; Schuster, M. W.; Irwin, D.; Stadtmauer, E. A.; Facon, T.; Harousseau, J.-L.; Ben-Yehuda, D.; Lonial, S.; Goldschmidt, Hartmut; Reece, D.; et al. (Leukemia, 2008)
Renal impairment is associated with poor prognosis in multiple myeloma (MM). This subgroup analysis of the phase 3 Assessment of Proteasome Inhibition for Extending Remissions (APEX) study of bortezomib vs high-dose dexamethasone assessed efficacy and safety in patients with relapsed MM with varying degrees of renal impairment (creatinine clearance (CrCl) <30, 30-50, 51-80 and >80 ml min−1). Time to progression (TTP), overall survival (OS) and safety were compared between subgroups with CrCl ⩽50 ml min−1 (severe-to-moderate) and >50 ml min−1 (no/mild impairment). Response rates with bortezomib were similar (36-47%) and time to response rapid (0.7-1.6 months) across subgroups. Although the trend was toward shorter TTP/OS in bortezomib patients with severe-to-moderate vs no/mild impairment, differences were not significant. OS was significantly shorter in dexamethasone patients with CrCl ⩽50 vs >50 ml min−1 (P=0.003), indicating that bortezomib is more effective than dexamethasone in overcoming the detrimental effect of renal impairment. Safety profile of bortezomib was comparable between subgroups. With dexamethasone, grade 3/4 adverse events (AEs), serious AEs and discontinuations for AEs were significantly elevated in patients with CrCl ⩽50 vs >50 ml min−1. These results indicate that bortezomib is active and well tolerated in patients with relapsed MM with varying degrees of renal insufficiency. Efficacy/safety were not substantially affected by severe-to-moderate vs no/mild impairment.
Gesehen am 21.01.2022